Pendidikan sebagai Kunci Peningkatan Kualitas Hidup: Peran Guru dalam Membuka dan Menutup Pembelajaran Fikih untuk Meningkatkan Keaktifan Belajar Siswa - Hamdani, Hamdani (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study employs a qualitative approach to understand the implementation of Islamic values and teacher performance in Islamic educational institutions. The research was conducted at MA Al Mufid, focusing on teachers' skills in opening and closing lessons and their impact on students' learning engagement. Primary data sources included teachers, students, and staff, while secondary data consisted of documented school records. Data were collected through direct observation, interviews, and document reviews, then analyzed using a qualitative descriptive method. The findings revealed that teachers' skills in opening lessons, such as capturing students' attention, presenting learning objectives, and conducting apperception, significantly contributed to student motivation and engagement. Meanwhile, closing skills, including reviewing lessons, evaluating, and providing follow-up activities, helped students understand and apply the material learned. However, some skills, such as the use of teaching aids and apperception, were not yet fully optimized. Data validity was ensured through triangulation and other methods to verify the accuracy of findings. This study highlights the importance of enhancing teachers' skills to support effective and sustainable learning processes.